2015
DOI: 10.1371/journal.pone.0125277
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Effects of siRNA against TMPRSS2-ERG Junction Oncogene in Prostate Cancer

Abstract: TMPRSS2-ERG junction oncogene is present in more than 50% of patients with prostate cancer and its expression is frequently associated with poor prognosis. Our aim is to achieve gene knockdown by siRNA TMPRSS2-ERG and then to assess the biological consequences of this inhibition. First, we designed siRNAs against the two TMPRSS2-ERG fusion variants (III and IV), most frequently identified in patients’ biopsies. Two of the five siRNAs tested were found to efficiently inhibit mRNA of both TMPRSS2-ERG variants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…As previously described and discussed in our latest paper, 15 in vitro , the NPs siRNA TMPRSS2-ERG-SQ were unable to enter within the cells without a transfecting agent. But we already demonstrated that they are still active after bio-conjugation with squalene despite the chemical modifications.…”
Section: Discussionsupporting
confidence: 52%
“…As previously described and discussed in our latest paper, 15 in vitro , the NPs siRNA TMPRSS2-ERG-SQ were unable to enter within the cells without a transfecting agent. But we already demonstrated that they are still active after bio-conjugation with squalene despite the chemical modifications.…”
Section: Discussionsupporting
confidence: 52%
“…Several approaches to targeting ERG activity are currently in the early phases of development. Urbinati et al have used TE fusion junction targeted siRNAs, similar to our approach, delivered via conjugation to squalene and self‐organization into nanoparticles. Treatment with these nanoparticles resulted in decreased VCaP tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that androgen deprivation alone will decrease TE fusion gene expression but TE re-expression is seen in castration-resistant PCa 36 due to a variety of alterations such as androgen receptor mutation Several approaches to targeting ERG activity are currently in the early phases of development. Urbinati et al 37 have used TE fusion junction targeted siRNAs, similar to our approach, delivered via conjugation to squalene and self-organization into nanoparticles. Treatment with these nanoparticles resulted in decreased VCaP tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Santoni et al indicated that fully understanding the role of TMPRSS2-ERG is important for individualised therapy in PCa patients (11). urbinati et al designed a kind of siRNA anti-TMPRSS2-ERG and successfully downregulated the expression of this fusion gene, and observably inhibited the proliferation of PCa cells (12). The above showed the potential and importance of TMPRSS2-ERG in PCa targeting treatment.…”
Section: Discussionmentioning
confidence: 99%